A relationship between job satisfaction, leadership style and stress among nurses (A study in Hospital Sultanah Bahiyah, Alor Setar, Kedah) - Premadevi, S. Balakrishnan (2013)
The purpose of the study is to evaluate the relationship between job satisfaction, leadership style and stress among nurses in hospital Sultanah Bahiyah. Data were collected succesfully from 269 nurses of Hospital Sultanah Bahiyah and data were analysed through questionaire. Job Satisfaction questionaire were adopted from Minnesota Satisfaction Questionaire (MSQ-Short Form) (1977), whereas Multifactor Leadership Questionnaire were adopted to measure the leadership style. The Multifactor Leadership Questionnaire were developed by Bernard M. Bass in 1985 and was revised several times through subsequent research. For stress, the questionnaire were adopted from DASS Stress Scale Questionnaire which were developed by Lovibond S.H and Lovibond P.F in 1995. The data from the questionnaire were analysed by using Statistical Package for Social Science(SPSS) version 20. Correlation analysis were performed to examine the relationship between job satisfaction ,leadership style and stress. The result shows there is a statistically significant relationship between job satisfaction and leadership style and moderately strong positive relationship between leadership style and stress. At the findings, recommendations and implication for future research were also disscussed